Examining the teaching and learning resources related challenges facing small and medium-sized public secondary schools in Kenya: A comparative analysis - Makori, Andrew; Onderi, Henry (Net Journals, 2014)
This article reports on the quantitative research survey findings regarding the challenges related to the teaching and learning resources affecting small and medium sized public secondary schools in Kenya. The aim of this study is to investigate the secondary school principals’ views on the teaching and learning resources related challenges facing small and medium sized secondary schools. The study took place in Nyamira County and adopted a quantitative survey design. The study is a quantitative survey involving 81 public secondary school principals. Questionnaires (both open and closed-ended, and rating scale items) were used to collect data. The resulting data was analysed using Statistical Package for Social Science (SPSS) producing descriptive data. 14.4 and 4.8% of small and medium sized secondary schools respectively lack a library resource; 8.4 and 2.4% of small and medium sized secondary schools respectively lack laboratory resource and one small school lack a sports facility. Besides, 16.8 and 19.2% of small and medium sized secondary schools respectively assessed library as poor or average; 26.4 and 21.6% of small and medium sized secondary schools respectively assessed the laboratory resource as poor or average; 21.6 and 15.6% small and medium sized secondary schools respectively assessed classroom as poor or average; 27.6 and 14.4% of small and medium sized secondary schools respectively assessed furniture as poor or average; 27.6 and 19.2% of small and medium sized schools respectively assessed staffing level as poor or average and 27.6 and 18% of small and medium sized secondary schools respectively assessed workshops as poor or average. Other resources assessed as poor or average include playgrounds and sports facility. In conclusion, some small and medium sized secondary schools lack library, laboratory and sports facility. Other small and medium sized secondary schools charged all the teaching and learning resources considered in this article unfavourably suggesting some concerns about them in relationship to teaching and learning process.
Keywords: Resources; Small and medium-sized schools; Public secondary schools; Challenges; Kenya